FORMING THE CREATIVE SKILLS OF PRIMARY CLASS STUDENTS ON THE 4K MODEL - Sayliyeva M. M. (European Science Publishing, 2024)
The article discusses the issue of forming the creative skills of primary school students on the 4K model.
Keywords: elementary, education, skills, 4K, creativity, knowledge, skills, approach, methodology.